Growth profile of multi-resistant strains in the ICU’s of a reference hospital in tropical diseases - Soares de Souza , Everton Raí; Pimentel de Carvalho, Sergio; Leite Pereira, Bianca; Amorim Esquerdo, Katia Maria; Rodrigues Pereira, Jefta; de Sousa Silva, Raynara Karen; Oliveira da Fonseca, Iraide; Arraes Pedrosa Barreto, Antônio Salles; Pimentel Assis, Ronny; Portela de Azevedo, Arimatéia (Revista Feridas, 2022)
Introduction: Health Care-Related Infections (HAI) are adverse events that are still persistent in health services. It is known that the infection leads to a considerable increase in the costs of patient care, in addition to increasing the length of stay, morbidity and mortality in the country’s health services. Objective: To record the growth profile of multidrug-resistant strains in immunosuppressed patients admitted to the ICU of a reference hospital for Tropical Diseases over a period of five years. Methodology: The present study was retrospective, descriptive and quantitative. Results: From January 2016 to December 2021, 245 HAIs were recorded, of which 73.3% were nosocomial respiratory tract infections-PAVM, 16.9% were urinary tract infections and 9.8% bloodstream. Regarding the resistance profile, the microorganisms that presented the greatest antimicrobial resistance power in the last 5 years were Klebsiella pneumonieae and Pseudomonas aeruginposa and E. coli. Conclusion: to prevent nosocomial infection, the main recommendations involve habits and care of patients and health professionals, in addition to adherence to the internal protocols of health services.